Physical, Textural, and Antioxidant Properties of Extruded Waxy Wheat Flour Snack Supplemented with Several Varieties of Bran. Issue 11 (28th September 2016) - Fleischman, Emily F.; Kowalski, Ryan J.; Morris, Craig F.; Nguyen, Thuy; Li, Chongjun; Ganjyal, Girish; Ross, Carolyn F.
Abstract: Wheat represents a ubiquitous commodity and although industries valorize 10% of wheat bran, most of this antioxidant‐rich byproduct gets fed to livestock. The objective of this study was to incorporate wheat bran into an extruded snack. Bran samples from hard red spring, soft white club cv. Bruehl, and purple wheat lines were added to cv. Waxy‐Pen wheat flour ( Triticum aestivum L.) at replacement concentrations of 0%, 12.5%, 25%, and 37.5% (w/w; n = 10). Extrudates were evaluated for antioxidant capacity, color, and physical properties. Results showed that high fiber concentrations altered several pasting properties, reduced expansion ratios ( P < 0.0001), and created denser products ( P < 0.0001), especially for white bran supplemented extrudates. Purple bran supplemented extrudates produced harder products compared to white and red bran treatments ( P < 0.0001). Extrudates produced with 37.5% (w/w) of each bran variety absorbed more water than the control with no added bran. The oxygen radical absorption capacity assay, expressed as Trolox Equivalents, showed that extrudates made with addition of red (37.5%) and purple (37.5%) bran had higher values compared to the other treatments; the control, red, and white bran treatments had less antioxidant activity after extrusion ( P < 0.0001) compared to purple bran supplemented extrudates. Purple and red brans may serve as viable functional ingredients in extruded foods given their higher antioxidant activities. Future studies could evaluate how bran variety and concentration, extruded shape, and flavor influence consumer acceptance.